BASLAWÍSH KLASS OQÍWSHÍLARÍNÍŃ KREATIV PIKIRLEW KÓNLIKPELERIN QÁLIPLESTIRIW USÍLLARÍ - Paluaniyazova, S.K. (SCIENCE and SOCIETY, 2025)
The article discusses ways to form and develop creative thinking of primary school students. Students thinking, identification and stimulation of each student is the basis of the study.
Keywords: creative; critical thought; category; contrivance; idea